A NEW MODEL FOR RAPID EVALUATION OF THE DEGREE OF LONG-CHAIN BRANCHING IN POLYMERS - SEO, YS; KIM, KU (ELSEVIER SCI LTD, 1994)
A new model is proposed for rapid evaluation of the degree of long-chain branching in polymers, which correlates the intrinsic viscosity and the molecular weight. Intrinsic viscosity is expressed as a simple inverse tangent function of molecular weight. The model is based on the observation of theological behaviour of polymer melts and solutions. It can describe the intrinsic viscosity behaviour over a wider range than the Mark-Houwink equation. This model does not use trial and error procedure to decide the threshold molecular weight where the intrinsic viscosity starts to deviate from the Mark-Houwink relation. Calculation by the proposed model of the long-chain branching frequency of low density polyethylene shows good agreement with experimental results in the literature.
Keywords: MOLECULAR-WEIGHT; VISCOSITY